Intrapopulation heterogeneity of cell volume for the alga Attheya ussurensis under stress conditions - Victoria A. Kurochkina; Luara F. Tkebuchava (Известия ТИНРО, 2016)
Intrapopulation heterogeneity of cell volume is estimated for the diatom Attheya ussuriensis acclimated to 17.5 ‰ salinity after its transfer to the media with salinity 8.8 ‰ (hypoosmotic conditions), 35.0 ‰ (hyperosmotic conditions) and 17.5 ‰ (control) at different stages of growth, under conditions of different nutrients supply and interaction with the diatom Conticribra weissflogii . The samples of A. ussuriensis were collected in the Ussuri Bay (Japan Sea) from an area with pure culture of this species. The cell volume of A. ussurensis increased under conditions of optimal nutrient supply and decreased under shortage of nutrients, irrespective on salinity. However, the salinity influenced on variability of the cell volume; the intrapopulation heterogeneity was formed mainly by size variation of large cells. The cell volume probability distribution became more asymmetric at change of growth stages, for any salinity as well. Clustering of cell volume distribution did not depend on salinity and nutrient supply. Both asymmetry and clustering of cell volume distribution for A. ussuriensis were rather different between mono- and mixed cultures in hypo- and hyperosmotic conditions but were almost equal in the control.